investigação do uso de micro-ondas/solvente eutético profundo na síntese de 2-aminocromenos - Silva, Damião Alves dos Santos (2023)
Compounds that have a nucleus based on the pyran ring are well reported in the literature as potential and promising candidates to be used in several pharmacological applications, mainly in the formulation of drugs that perform analgesic, anticancer, antimicrobial and anti-HIV activities. In this context, efficient and easy-to-prepare synthetic routes that are less harmful to the environment and are processed without the use of catalysts have been developed for the synthesis of these compounds. With the intention of proposing a system with new reaction conditions for the synthesis of aminochromenes that have the pyran ring as their base unit, a synthetic route was developed in which it is processed in the absence of a catalyst and has the easily prepared eutectic mixture as the solvent in the reaction medium. , formed by choline chloride and urea, in addition to using microwave radiation as a heating source for the system. Thus, starting with the syntheses of compounds in a cascade reaction involving Knoevenagel condensation-Michael addition-intramolecular cyclization, which occurs between a carbonyl compound and an active methylene compound, we used salicylaldehyde and malononitrile as substrates, respectively, in a reaction medium with the presence of the eutectic solvent of ChCl/urea at a temperature of 60 ºC under microwave irradiation. Monitoring by CCD showed that the reagents were consumed in a timely manner of just 0.5 minutes. Several other salicylaldehydes with different substituent groups were used in order to verify the influence of these groups on the reaction kinetics to obtain different 2-amino-4H-chromenes. In all reactions, the reagents were quickly consumed, with time intervals that varied between 10 and 15 minutes depending on the salicylaldehyde used and their molar ratio with malononitrile. In the reactions between salicylaldehydes and malononitrile, in the proportion of 1:2, the formation of mixtures of two products derived from 2-amino-4H-chromenes (3a and 4a) was observed in which, through the HPLC analyses, it was verified that the The product in greater quantity is compound 4a, which until then could only be obtained from 3 equivalents of malononitrile. In the reactions between salicylaldehydes and malononitrile, in the molar ratio 1:3, the analyzes also showed a mixture of products for most of the reactions, with the desired products being formed in greater proportion (4a-4f). Attempts to purify the solids obtained in the synthesis resulted in the isolation of two products, 4a and 4e, which presented yields of 95% and 72%, respectively. The reaction system presented here and the conditions employed are efficient and can be easily used in aminochromene synthesis reactions.